The Effect of Financial Literacy, Financial Inclusion and Fintech Payment on The Performance of UMKM in Bandar Lampung City - Alkavi, Achmad Sonni Nahdlo; Amna, Luke Suciyati (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Research to see financial technology, financial inclusion, and financial literacy in influencing the performance of MSMEs in Bandar Lampung City. The population in this research is MSMEs in Bandar Lampung, the sample size is calculated using the Slovin technique, resulting in 100 MSME respondents. Primary data was collected through questionnaires, and the results of the questionnaire will be tested using SPSS 27 with a multiple linear approach. This study found that financial inclusion, financial literacy, and financial technology can positively influence the performance of MSMEs partially and simultaneously.